THE INITIATION PHASE OF TURKISH EDUCATION IN THE DEPTHS OF HISTORY (21 DECEMBER 1944) - Nuredin, Abdulmecit (International Scientific Journal Vision, 2023)
The right to education is the legal right of individuals to have the authority to learn, teach, receive education and selfdevelopment and use these powers as they wish. Regardless of the language, religion, sect, race, gender, ethnic origin and political view of the individual, it cannot be prevented from benefiting from basic education. The right to education is guaranteed by both national and international conventions and declarations. The concept of the right to education first came to the fore after the French Revolution of 1789 with the emergence of concepts such as freedom, equality and fraternity. The understanding of the social state that emerged later considered education and training as one of the primary duties of the state. It is one of the duties of the social state that the nation receives a scientific, useful, creative and democratic education under equal conditions. On the eve of the end of the Second World War, a serious breakthrough was made in the field of education with the establishment of Yugoslavia in order to enter the effects of the permanent war and to realize social development. The education mobilization in question has a universal character, covering many nationalities and based on the realities of the period. In this article, the study, which includes the acquisition and development of Turkish education in 1944, constitutes the basis of the study. In this article, the study, which includes the acquisition and development of Turkish education in 1944, constitutes the basis of the study.